Welfare transitions before and after reforms of the German welfare system - Christoph Wunder; Regina Riphahn (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We study state dependence in the German welfare system and compare transition patterns before and after recent reforms of the welfare system (Hartz Reforms). Using data from the German Socio-Economic Panel, we apply dynamic multinomial logit estimators and find that welfare transitions have generally not changed significantly after the reform: the probabilities of welfare entry and welfare exit increased only slightly whereas the probability of welfare persistence declined somewhat. After the reform, welfare persistence and welfare-to-employment transitions of immigrants became more responsive to the labor market situation.
Keywords: I38; J61; C23; 330